The 4Ps in Anini-y, Antique its implementation and effects in upland communities. - Arbolado, Essa Mae S.
This study discusses and analyzes the Pantawid Pamilyang Pilipino Program (4Ps), its implementation and effects to beneficiaries? access to basic services (education and health) and economic well-being. A total 57 4Ps beneficiaries were surveys, in three barangays in Anini-y, Antique. Survey data were supplemented with key informant interviews and secondary data review. The study shows that the 4Ps enhanced beneficiaries? access to education and health services. This is manifested by consistent data on school participation and promotion rate of students beneficiaries and by children?s regular visit to health centers to monitor their health conditions. The same can be said for pregnant mothers who benefited from the program. The program was also deemed responsible for improving household conditions of beneficiaries particularly in terms of enhanced purchasing power as testimonies by the respondents say that they now have the money to purchase basic need which is food. The 4Ps provides direct benefits to beneficiaries but the process of implementation could have been improved by way of establishing objective and clearer targeting criteria, non-politicization of the process of selection and improving systems for monitoring to ensure compliance to conditionalities. The study suggests the infusion of community-based and participatory principles into the program to enhance local accountability and compliance.